Ecology of Prognathodes obliquus, a butterflyfish endemic to mesophotic ecosystems of St. Peter and St. Paul's Archipelago - Nunes, Lucas T.; Cord, Isadora; Francini-Filho, Ronaldo B.; Stampar, Sergio N. [UNESP]; Pinheiro, Hudson T.; Rocha, Luiz A.; Floeter, Sergio R.; Ferreira, Carlos E. L. (Springer, 2019)
Chaetodontidae is among the most conspicuous families of fishes in tropical and subtropical coral and rocky reefs. Most ecological studies focus in the genus Chaetodon, while Prognathodes remains poorly understood. Here we provide the first account on the ecology of Prognathodes obliquus, a butterflyfish endemic to St. Peter and St. Paul's Archipelago (SPSPA), Mid-Atlantic Ridge. We studied the depth distribution and foraging behaviour of P. obliquus through technical diving, remote-operated vehicles and submarines. Also, we characterized its diet by analysing stomach contents. Prognathodes obliquus is mostly found below 40 m, with abundance peaking between 90 and 120 m and deepest record to date at 155 m. It forages mostly over sediment, epilithic algal matrix and complex bottoms formed by fused polychaete tubes, preying mostly upon polychaetes, crustaceans, hydroids and bryozoans. Branching black corals were rarely consumed and used mostly as refuge. In conclusion, P. obliquus is a generalist invertebrate feeder typical of mesophotic ecosystems of SPSPA.
Keywords: Chaetodontidae; Diet; Deep reefs; Microplastics; Mid-Atlantic Ridge; St. Paul's Rocks